The Decoupling of Managers' Self-interest and Implementation Performance: An Agency Theory Perspective. - Qiu, Yarong (2008)
This thesis focuses on how to minimize the self-interest of the managers' behavior in strategy implementation (SI), to achieve principal-interest maximization. Agency theory is used to predict the related factors of managers' behavior, and in order to fill the gaps of agency theory in Asian countries, especially in China, this thesis introduces Guanxi in China with supplements from telephone interviews in 50 companies. Additionally, it assumes the related factors of the SI managers' self-interest, predicts their interrelationships, and develops a model based on these related factors. Based on a survey of 655 organizations, the research tests the developed model to extrapolate factors related to the SI managers' self-interest and strategy implementation performances. Furthermore, the research aims to provide implications on how to minimize the SI managers' self-interest in the strategy implementation processes, while also aiming to prove whether the minimization of the SI managers' self-interest in the strategy implementation processes will contribute to higher degrees of strategy implementation performances. The findings, based on the questionnaires' results, provide strong support that minimization of the SI managers' self-interest leads to higher strategy implementation performances. In summary: Organizational culture, performance measurements and incentives are determinants of the SI managers' self-interest. The SI managers' participation in the strategic decision-making stages, shapes organizational culture indirectly affecting the SI managers' self-interest. To improve strategy implementation performances, apart from minimizing the SI managers' self-interest, the effects of Guanxi between principals and managers, and performance measurements and incentives are limited. In addition, this research reveals that the SI managers' attitude toward strategic risk is critical to strategy implementation performances.